(18)F-Fluoride PET/CT tumor burden quantification predicts survival in breast cancer - Brito, Ana E. (Oncotarget, 2017)
PURPOSE: In bone-metastatic breast cancer patients, there are no current imaging biomarkers to identify which patients have worst prognosis. The purpose of our study was to investigate if skeletal tumor burden determined by (18)F-Fluoride PET/CT correlates with clinical outcomes and may help define prognosis throughout the course of the disease. RESULTS: Bone metastases were present in 49 patients. On multivariable analysis, skeletal tumor burden was significantly and independently associated with overall survival (p < 0.0001) and progression free-survival (p < 0.0001). The simple presence of bone metastases was associated with time to bone event (p = 0.0448). MATERIALS AND METHODS: We quantified the skeletal tumor burden on (18)F-Fluoride PET/CT images of 107 female breast cancer patients (40 for primary staging and the remainder for restaging after therapy). Clinical parameters, primary tumor characteristics and skeletal tumor burden were correlated to overall survival, progression free-survival and time to bone event. The median follow-up time was 19.5 months. CONCLUSIONS: (18)F-Fluoride PET/CT skeletal tumor burden is a strong independent prognostic imaging biomarker in breast cancer patients.